Osthole Suppresses Cell Growth of Prostate Cancer by Disrupting Redox Homeostasis, Mitochondrial Function, and Regulation of tiRNAHisGTG - Jisoo Song; Jiyeon Ham; Gwonhwa Song; Whasun Lim (MDPI AG, 2024)
Prostate cancer remains a significant global health concern, posing a substantial threat to men's well-being. Despite advancements in treatment modalities, the progression of prostate cancer still presents challenges, warranting further exploration of novel therapeutic strategies. In this study, osthole, a natural coumarin derivative, inhibited cell viability in cancer cells but not in the normal prostate cell line. Moreover, osthole disrupted cell cycle progression. Furthermore, osthole reduces mitochondrial respiration with mitochondrial membrane potential (ΔΨm) depolarization and reactive oxygen species (ROS) generation, indicating mitochondrial dysfunction. In particular, osthole-induced ROS generation was reduced by N-acetyl-L-cysteine (NAC) in prostate cancer. In addition, using calcium inhibitors (2-APB and ruthenium red) and endoplasmic reticulum (ER) stress inhibitor (4-PBA), we confirmed that ER stress-induced calcium overload by osthole causes mitochondrial dysfunction. Moreover, we verified that the osthole-induced upregulation of tiRNAHisGTG expression is related to mechanisms that induce permeabilization of the mitochondrial membrane and calcium accumulation. Regarding intracellular signaling, osthole inactivated the PI3K and ERK pathways while activating the expression of the P38, JNK, ER stress, and autophagy-related proteins. In conclusion, the results suggest that osthole can be used as a therapeutic or adjuvant treatment for the management of prostate cancer.